Sustainable Development: Implementation of the Jama'i Method In Producing Quran Memorizers - Rohmah, Mutia Mawaddah; Lutfiyani; Lasman Azis (Al-Kahfi: Jurnal Pendidikan Agama Islam, 2024)
One aspect that teachers need to pay attention to in producing Quran memorizers is the use of appropriate methods according to the diversity of students. The appropriate method is easy to understand, comprehend, and implement in memorizing the Quran, so that students are not burdened by the method used by the teacher. This study aims to analyze the steps taken by teachers and students to memorize the Quran using the jama'i method. This study uses a qualitative method with a case study design approach. Data sources were collected through in-depth individual interviews with seven informants consisting of the head of the institution, teachers, and students at one of the institutions where students memorize the Quran. All informants were selected by purposive sampling at the location where this study was conducted. In addition, data were also collected through direct observation of the entire series of teachers and students during Quran memorization. Document analysis was also conducted related to the documents needed for this research data. All data were analyzed using the interactive technique of Miles and Huberman. The research findings show four steps in implementing the jama'i method to produce students who memorize the Quran. The four steps are i) improving the recitation of the Qur'an according to the rules of tajwid, ii) memorizing the Qur'an, iii) tasmi' (listening) the memorization to the teacher and iv) at the end of the activity the students are tested on their memorization of the Qur'an by the supervising teacher. The four steps as practiced in the jama'i method in memorizing the Qur'an by students in this finding can be used as an example by prospective Qur'an memorizers, because it has been proven successful in producing Qur'an memorizers at the institution where this research was conducted.